ANALISIS PUTUSAN GUGATAN PERWAKILAN KELOMPOK SEBAGAI UPAYA MENDAPATKAN MENDAPATKAN JAMINAN PERLINDUNGAN HAK ATAS TANAH (Studi Putusan No. 262.Pdt.G/Class.Action/2016/PN.Jkt.Pst) - Itok Dwi Kurniawan; Azis Akbar Ramadhan; Geby Christabella Randa; Kristiana Widiawati; Septian Joddie Dwianur Sukono (Jurnal Hukum Mimbar Justitia, 2020)
Examine more deeply regarding Class Action Filing in Indonesia which is regulated in the Supreme Court Regulation No.1 of 2002., in this analysis one of the decisions is 262.Pdt.G / Class.Action / 2016 / PN.Jkt.Pst, The decision contains a group of residents of DKI Jakarta Selatan, consisting of several groups, jointly filing a lawsuit against the law (1365 BW) against related agencies which are deemed to have caused material and immaterial losses due to the normalization of the Ciliwung River. The research used is normative descriptive and literature study. In this study will examine the Considerations of the Panel of Judges regarding the Guarantee of Protection of Land Rights based on the Basic Agrarian Law and the Law on Land Acquisition. The result of this research is that the Judge's Decision does not accommodate the Plaintiffs, so that the aspects of justice that live in the eyes of the community are not fulfilled. Keywords: Lawsuit Group Representatives, Judge's Consideration, Land Rights.